PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, LIKUIDITAS DAN GROWTH OPPORTUNITY TERHADAP NILAI PERUSAHAAN - Sopiah, Siti (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThe purpose of this research is to find out firm size, profitability, and liquidity and growth opportunity to the firm value. In this research, the sample collection technique is determined by the amount of samples i.e. 10 automotive companies. This research applies multiple linear regressions analysis and the application SPSS 20 version.The result of this research shows that: (1) simultaneously the variables of firm size, Growth Opportunity, Liquidity, Profitability have influence to the firm value. (2) Partially firm size variable does not have any influence to the firm value. And the sign of the coefficient is positive which is shown by the linear correlation between firm size and firm value. (3) Partially Growth Opportunity variable does not have any influence to the firm value. The positive sign is shown by the correlation between Growth Opportunity and firm value. (4) Partially the Liquidity does not have any influence to the firm value with the negative sign shows direction between liquidity and firm value. (5) Partially profitability has influence to the firm value with the positive direction shows the linear direction between profitability and firm value.Keywords: Firm Size, Growth Opportunity, Liquidity, Profitability, Firm Value.